Molecular changes in phenolic compounds in Euglena gracilis cells grown under metal stress - Bernard, Eve; Guéguen, Céline (Frontiers in Plant Science, 2023)
Metal presence in the aquatic ecosystem has increased and diversified over the last decades due to anthropogenic sources. These contaminants cause abiotic stress on living organisms that lead to the production of oxidizing molecules. Phenolic compounds are part of the defense mechanisms countering metal toxicity. In this study, the production of phenolic compounds by Euglena gracilis under three different metal stressors (i.e. cadmium, copper, or cobalt) at sub-lethal concentration was assessed using an untargeted metabolomic approach by mass spectrometry combined with neuronal network analysis (i.e. Cytoscape). The metal stress had a greater impact on molecular diversity than on the number of phenolic compounds. The prevalence of sulfur- and nitrogen-rich phenolic compounds were found in Cd- and Cu-amended cultures. Together these results confirm the impact of metallic stress on phenolic compounds production, which could be utilized to assess the metal contamination in natural waters.